Interpreting the law: a reassessment of the dichotomy between the law and its readings - Polat, Necati (1993)
The purpose of this thesis is to pursue a grammatical, common sense, reading of some of the contemporary accounts of the workings of law. In so doing it relies extensively on the critical work by Heidegger, Wittgenstein, Derrida, and Stanley Fish, writers assumed to present a somewhat unified perspective on such matters as understanding, language, meaning and reading. The shorter of the two parts, 'Judgement, Criteria, Justice,' sets the stage. Looking at Jean-Franςois Lyotard's discourse, in Just Gaming, of a semantic and moral apocalypse, and his subsequent search for a concept of the just, the first part introduces the principal themes of the essay. These themes at once form some of the major concerns of the contemporary legal theory; the text of the law, the authorial intention, the politics of interpretation, the interpreter, and the limits of interpretation. Chapter 1.1 probes the concept of authorship as formulated by Lyotard. According to him, the modern situation produces a concept of the author that is detached. The modem situation lacks the transparency that characterizes the classical situation, where the author and the reader could relate to one another, and where, therefore, interpretation was a possibility. The Lyotardian concept radically distinguishes between the realms of the author and of the audience, a distinction that suppresses the ineluctably fraternal, attached quality of authorship. Chapter 1.2 is a critique of the concept of judgement Lyotard advances. It explores the two distinct orders within which, according to Lyotard, judgement is practicable: those of faith ('the Jewish pole') and paganism. While both orders exclude the concept of an autonomous subject - a false order which defines the rhetoric of the mainstream Western thought - the homogenous formalism of one, faith, contrasts with the heterogenous localism of the other, the pagan attitude. Questioning the dichotomy, the discussion goes on to argue for a concept of the primordiality of the attached, situated, quality of both the issuing of the judgement and of its possible interpretations, irrespective of the distinct orders of rhetoric – autonomous, heterogenous, religious - in which they are presented. Chapter 1.3 explores the Lyotardian reworking of Kant's categorical imperative and seeks to point out the problematic nature of the enterprise. The discussion questions the idea that a thematic, non-moral, non-political, concept of the just may necessarily function better than one which is of common opinion, and indicates the illusory character of the Lyotardian venture radically to contrast what would be a thematic concept of the just with that which is mere common opinion. Chapter 1.4 continues on the subject of the politics of interpretation - can what would be the unruly, fantastic dictates of morals be avoided on the basis of a universalistic, politics-free, criterion? - to test the opposition Lyotard draws between the Sophistic and the Kantian positions. While from the Sophistic viewpoint a genuine opposition of competing moralities is not a possibility, the Kantian morality makes conceivable the concept of a rational, as opposed to mere opinion-based and rhetorical, choice. The longer part, The Law and Its Readings,' is a reading of some of the motifs of Franςois Gény's Method of Interpretation and Sources of Private Positive Law. Each of the four chapters that make the second part aims to dissolve one of the four binary oppositions that characterize the contemporary scene - polarities that are strictly mere variations on the theme of the dichotomy between the law and its readings, the law and that which is made of it: the text and the extratext, intention and extension, the tame and the freakish, the real and the formal. In the four chapters that form the second part, the logic behind the oppositions is explored, and a grammatical reassessment, which indicates the terms of each one of the polarities ultimately metamorphic and elusive, though, naturally, of possible grammatical use, is suggested. Chapter 2.1 examines some of the contemporary arguments relating to the text of the law. Extratextualist positions such as, famously, Gény's counter the mainstream textualist positions by arguing against the mechanistic conception of the law that is written, all inclusive, and once and for all. Curiously, however, the notion of the law therefore invoked presupposes a notion of the text which might best suit the formalism of the mainstream positions - namely that the text, as opposed to what might tentatively be called history, is the locus of meaning. What follows this markedly positivistic notion of the text, a notion invoked in particular in the extratextualist positions on the interpretation of the American Constitution, is a fear of judgement that would be made on the basis of what is often (as in the segregation cases) an obsolete concept embodied in the text. This fear, in fact, is not different from the formalistic, mainstream-textualistic, fear of what would become of the law in the absence of formally circumscribed, textual, constraints. In exploring the theme, the discussion focuses on certain individual cases, such as the segregation cases of the U.S. Supreme Court, arguments over which have been an integral part of the theory. Chapter 2.2 is devoted to the considerations of the legislative will. Counterintentionalist positions regarding the interpretation of the law, it argues, may in fact suggest an inherent intentionalism, as epistemologically understood, which may in turn point in the direction of a reversal not dissimilar to that of the binary opposition of textualism and extratextualism. The traditional arguments against the mainstream intentionalism seem to gather on two points: first, that intention is a state of mind and therefore impossible to uncover for those who do not have a natural access inside others' heads; and secondly, that even if it were possible to uncover it, what one has with the legislative will is but a fiction, for it refers to, not one, but many minds who could not possibly intent one and the same thing. The discussion seeks to disclose the way counter-intentionalist arguments subscribe to traditional intentionalism by assuming intention as an occult presence, to use two concepts, one Wittgesteinean and one Derridean, together. And it argues how intention as a concept is a possibility precisely because it is in each case a collegiate, fraternal extension. Chapter 2.3 explores the problems of judicial discretion, politics, and the politics of interpretation. It discusses some of the traditional criticisms of judicial review, in particular the countermajoritarian objection, and points out the metamorphic character of some of the positions in the debate. In that countermajoritarianism refuted from a majoritarian viewpoint stands right behind the very idea of constitutionalism, a distinct refuge at once of the majoritarian positions. And the positions that resist the idea of a timid, majoritarian, judiciary appear to be equally paradoxical, for these positions are simply for being ill at ease with the constitutional principle that is countermajoritarianism par excellence. The discussion then focuses on the Dworkin-Fish debate on the politics of interpretation and at once attempts to pin down some of the veins in Dworkin's thinking on the subject of judicial licence. An overall evaluation of the conceptual scheme, potentialities, and assumptions of legal realism is attempted in chapter 2.4. Realism appears to emphasize the part of the interpreter, as opposed to the text, in the event of adjudication, and question the traditional assumptions of formalism whose mechanistic concept of jurisprudence equates the law with its text. While some of the most crucial of the realist objections to the formalistic concept of adjudication have been genuine and insightful. The realist writers, however, have been for the most part unaware of some of the formalistic, and ultimately self-refuting, presuppositions of their own rhetoric. It is argued that realism betrays its very rationale and mimics the mainstream formalism as it effectively supplants the formalistic considerations of the law as a system of rules, a text-oriented enterprise, with its preoccupations of the law as the right methodology. What may be called a thematic correctionism has marked realism in its distinct patterns across diverse terrains of jurisprudence. Finally, concluding, the essay questions the validity of its own discourse and, offering a reappraisal of the dichotomy that marks the concept of a critical enterprise. namely that of the same and the similar, that which is and its representation, indicates its own limits. The idea is then tested against some of the recent attempts to evade the limitations and consequences of one's own discourse as a rhetorical exercise. The concluding chapter, therefore, is intended to balance, as it were, the discourse and hint at its own conditions of validity as an exercise in rhetoric. Some more explicit - traditional - conclusions are nevertheless drawn.